Preface of 2024 IEEE 4th International Conference on Electronic Communications, Internet of Things and Big Data (IEEE ICEIB 2024) - Teen-Hang Meen; Shu-Han Liao; Cheng-Fu Yang (Engineering Proceedings)
This volume presents the proceedings of the 2024 IEEE 4th International Conference on Electronic Communications, Internet of Things, and Big Data (IEEE ICEIB 2024) [...]